Proposed Reconstructions of Cases Six and Eight of the Edwin Smith Papyrus - Chapman, Paul.
From a medical–historical perspective, Case Eight of the Edwin Smith Papyrus is one of the most important in that document. It graphically describes hemiplegia resulting from a closed head injury and distinguishes it from other nontraumatic conditions that might be associated with similar neurologic deficits. It is also one of the longest cases in the manuscript, due largely to an extended concluding passage that is virtually identical to the description of a horrific open skull fracture contained in Case Six. There is no unanimity regarding the significance of this unusual passage, which deviates from the otherwise rigidly applied format of the case presentations. The manuscript’s grammatical framework is as ordered as its compositional structure otherwise. The method employed in the present study is to analyze Cases Six and Eight in this light in order to identify textual peculiarities common to both that might give a better understand of the relationship between them. Based on this analysis I propose a reconstruction of each case that addresses semantic and syntactic anomalies in the sole existing copy of the document and discuss possible implications of our conclusions for its organization and revision over time.